1999
DOI: 10.1097/00000539-199905000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Infusion Improves Neutrophil Function in Diabetic Cardiac Surgery Patients

Abstract: A continuous insulin infusion and glucose control during surgery improves white cell function in diabetic patients and may increase resistance to infection after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(66 citation statements)
references
References 22 publications
2
62
0
2
Order By: Relevance
“…30,[55][56][57][58] Generation of free radicals is reportedly as an important organismal defense mechanism during infectious processes. 30,51,59,60 In this work, it was found that both MEs of Brazil Nut oil increased the release of superoxides from human blood phagocytes.…”
Section: Figure 2 Pseudoternary Diagrams Indicating Microemulsion (1mentioning
confidence: 99%
“…30,[55][56][57][58] Generation of free radicals is reportedly as an important organismal defense mechanism during infectious processes. 30,51,59,60 In this work, it was found that both MEs of Brazil Nut oil increased the release of superoxides from human blood phagocytes.…”
Section: Figure 2 Pseudoternary Diagrams Indicating Microemulsion (1mentioning
confidence: 99%
“…Continuous insulin infusion might improve the impaired neutrophil function observed in DM. 53,54 During the peritransplant period, enormous stress/inflammation or corticosteroids can induce insulin resistance, which leads to hyperglycemia owing to an insufficient insulin secretion to overcome such insulin resistance. CNI also decreases the secretion of insulin by pancreatic β cells.…”
Section: Ptdm and Clinical Outcomesmentioning
confidence: 99%
“…The reduction in infectious diseases by IGC may reflect the deleterious effects of hyperglycemia on macrophage or neutrophil function or insulin-induced protective effects on mucosal and skin barriers. [24][25][26][27] The improvement of innate immunity could be quite important, especially during the period of granulocytopenia after allogeneic HSCT. The protection of mucosal tissues could reduce bacterial translocation, which might lead to a reduced incidence of sepsis.…”
Section: Intensive Glucose Control After Hsct S Fuji Et Almentioning
confidence: 99%